Jogos: uma abordagem matemática. - Pontes, Max Maia Attanasio Voss (2018)
This dissertation addresses four mathematical games, namely: Game of Nim, Resta One, Jumping Frog and Game of Wythoff. A historical, exemplary and illustrative approach is taken. Soon after, it is shown, with mathematical rigor, how the winning algorithm of each game works.